2019
DOI: 10.1002/adfm.201808291
|View full text |Cite
|
Sign up to set email alerts
|

Yolk–Shell Structured FeP@C Nanoboxes as Advanced Anode Materials for Rechargeable Lithium‐/Potassium‐Ion Batteries

Abstract: Maintaining structural stability and alleviating the intrinsic poor conductivity of conversion-type reaction anode materials are of great importance for practical application. Introducing void space and a highly conductive host to accommodate the volume changes and enhance the conductivity would be a smart design to achieve robust construction; effective electron and ion transportation, thus, lead to prolonged cycling life and excellent rate performance. Herein, uniform yolk-shell FeP@C nanoboxes (FeP@CNBs) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
166
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(176 citation statements)
references
References 37 publications
10
166
0
Order By: Relevance
“…As the current density rolls back to 0.1 A g −1 , the specific capacity can be returned to 331.1 mAh g −1 . The above results indicate that the ED‐MoS 2 @CT electrode possesses the superior potassium storage properties, which are not only superior to the contrast samples (for the detail information, see Figure S12 in the Supporting Information) but also comparable for most previously reported PIB anode materials (Figure e) . Notably, the fabricated ED‐MoS 2 @CT electrode exhibits the outstanding cycling stability at high current densities.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As the current density rolls back to 0.1 A g −1 , the specific capacity can be returned to 331.1 mAh g −1 . The above results indicate that the ED‐MoS 2 @CT electrode possesses the superior potassium storage properties, which are not only superior to the contrast samples (for the detail information, see Figure S12 in the Supporting Information) but also comparable for most previously reported PIB anode materials (Figure e) . Notably, the fabricated ED‐MoS 2 @CT electrode exhibits the outstanding cycling stability at high current densities.…”
Section: Resultssupporting
confidence: 65%
“…However, the reversible capacity and the cycling stability of most materials are still unsatisfactory to meet the requirements of high energy density storage devices . Particularly, the intrinsic larger ionic radius of K + (1.38 Å), in comparison to Li + (0.76 Å), causes the high mechanical stress/strain of host electrodes and the sluggish diffusion rate during K‐ion intercalation/de‐intercalation …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the existing pioneering work involving graphite, tremendous efforts have been devoted to this area of research. To date, several categories of materials are verified to be effective for potassium storage in terms of anodes, including carbon nanophases (eg, hard carbon, graphite, and heteroatom‐doped carbon), alloy‐type (semi‐)metals (eg, Sn, Bi, Sb, and P), metal oxides (eg, Nb 2 O 5 , SnO 2 , Fe x O, and Sb 2 MoO 6 )/sulfides (eg, MoS 2 , VS 2 , SnS 2 , and Sb 2 S 3 ) and phosphides (eg, FeP, CoP, Sn 4 P 3 , and GeP 5 ), sylvite compounds (eg, KVPO 4 F, K 2 V 3 O 8 , KTi 2 (PO 4 ) 3 , and K x Mn y O z ), metal‐organic composites (eg, Co 3 [Co(CN) 6 ] 2 and K 1.81 Ni[Fe(CN) 6 ] 0.97 ·0.086H 2 O), and pure organic polymers (eg, boronic ester, fluorinated covalent triazine, perylene‐tetracarboxylate, perylenetetracarboxylic diimide, azobenzene‐4,4′‐dicarboxylic acid potassium, 2,2′‐azobis[2‐methylpropionitrile], and poly[pyrene‐ co ‐benzothiadiazole]). However, most carbon materials barely deliver reversible capacities exceeding 300 mAh g −1 despite their excellent electrochemical cyclability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bai et al reported the fabrication of CoP nanoparticles embedded into nitrogen and phosphorus codoped porous carbon sheets, which exhibited outstanding electrochemical performance as an anode material for both SIBs and KIBs . Yang et al synthesized a yolk‐shell FeP@carbon nanoboxes with the inner FeP nanoparticles protected by a thin carbon outer shell, manifesting remarkable cyclic stability with no significant decay after 300 cycles . Nevertheless, the design of novel integrated nanoarchitectures between TMPs and doped carbons with sufficient volume change buffers and efficient electron/ion diffusion pathways for potassium‐ion storage, still remains quite challenging.…”
Section: Introductionmentioning
confidence: 99%